Pengaruh Konflik Politik Terhadap Studi Hadis Pasca Perang Shiffin - Muhammad Muhammad Anshori (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This paper attempts to explain the phenomenon of hadith studies during the Ṣiffīn war. In the history of Islamic civilization, conflict is always there, one factor that raises conflict is political associated with leadership issue. Even the first conflict occurred in Islam had it after the Prophet Muhammad died. This factor influenced relatively to the study of hadith. Islamic history has experienced